Comparison Of Intravitreal Triamcinolone Injection Vs Laser Photocoagulation in Angiographic Macular Edema in Diabetic Retinopathy - Somesh V Aggarwal; Sonali N Shah; Rekha M Bharwada; Puja S Negi; Nimesh M Jain (Medsci Publications, 2012)
Aims: To compare the effect of laser photocoagulation and intravitreal triamcinolone acetonide in the treatment of diabetic macular edema Material and Methods: During the period of one year 100 patients having diabetic macular edema were enrolled in the project. Fluorescein angiography was carried out in all patients to confirm the diagnosis of macular edema Patients were randomly assigned into two groups. One group was treated with laser photocoagulation and other group was given intravitreal triamcinolone. Observations: The patients registered in the project were in the age range of 40 to 76 years. The main outcome measures were visual acuity and macular edema on angiography. At three months patients receiving triamcinolone had better visual acuity compared to laser photocoagulation. However these findings were reversed by 12 months and laser photocoagulation remained superior to triamcinolone at the end of 1 year of follow up. Discussion: A similar study conducted by DRCR compared laser photocoagulation to intravitreal triamcinolone for treatment of diabetic macular edema. At four months, patients receiving intravitreal triamcinolone had better visual acuity compared to laser photocoagulation. These findings were reversed by 16 months, and laser photocoagulation remained superior to triamcinolone at three-year follow-up. Conclusion: To conclude our study showed that although intravitreal triamcinolone was successful in improving visual acuity in patients at the end of 3 months the effect was transient and in long term laser photocoagulation was more effective.